The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.24106/kefdergi.702904
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin Mutluluk Korkusu ve Duygularını İfade Etme Becerileri Arasındaki İlişkide Öz Duyarlılığın Aracı Rolü

Abstract: Bu araştırmanın amacı, üniversite öğrencilerinin mutluluk korkusu ve duygularını ifade etme becerileri arasındaki ilişkide öz duyarlılığın aracı rolünü incelemektir. Bu çalışmanın örneklemi Marmara Üniversitesi'nde 2017-2018 eğitimöğretim yılında çeşitli lisans programlarına devam eden ve tabakalı örnekleme yöntemi ile belirlenen 296 öğrenciden oluşmaktadır. Veri toplama araçları olarak, Kişisel Bilgi Formu, Mutluluk Korkusu Ölçeği, Özduyarlılık Ölçeği ve Duyguları İfade Etme Ölçeği kullanılmıştır. Araştırma y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(25 reference statements)
0
0
0
1
Order By: Relevance
“…As a matter of fact, fear of happiness is considered an anxiety disorder by some psychiatrists (Nall and Legg 2017). Individuals who experience fear of happiness are more submissive in their social relationships and tend to suppress their emotions more (Gilbert et al 2014, Ekşi et al 2020. They also show a more antisocial and maladaptive nature (Özkan 2020).…”
Section: Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a matter of fact, fear of happiness is considered an anxiety disorder by some psychiatrists (Nall and Legg 2017). Individuals who experience fear of happiness are more submissive in their social relationships and tend to suppress their emotions more (Gilbert et al 2014, Ekşi et al 2020. They also show a more antisocial and maladaptive nature (Özkan 2020).…”
Section: Symptomsmentioning
confidence: 99%
“…It has been found that fear of happiness is caused by some possible causes that occur in early childhood. Fear of happiness can be caused by a child being warned or punished when he or she has a positive emotion at an early age, growing up in a family that does not have healthy family patterns, feeling guilty for having fun in the presence of a sick family member, or developing early maladaptive schemas (Gilbert et al 2014, Ekşi et al 2020). Likewise, their positive emotions cause negative emotions in individuals whose needs cannot be met in a warm and sincere manner (Amiri et al 2019).…”
Section: Factors Leading To Fear Of Happinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatür incelediğinde yurt içinde ve dışında ergenlerin gelecek beklentisi (Arslan, 2014;Eryılmaz, 2011;Şimşek, 2012;Tuncer, 2011;Yavuzer, Demir, Meşeci ve Sertelin, 2005), psikolojik sağlamlığı (Arslan, 2015a, Arslan, 2015bCohn, Fredrickson, Brown, Mikels ve Conway, 2009;Gündaş ve Koçak, 2015;Kabasakal, 2014) ve mutluluk korkusunu (Demirci, Ekşi, Kardaş ve Dinçer, 2016;Ekşi, İkiz ve Başman, 2019;Gilbert vd., 2012;Jashanloo, 2013;Sarı ve Çakır, 2016;Tunç, 2020) ayrı ayrı konu edinen araştırmalar olduğu görülmektedir. Bununla birlikte gerek yurt içinde gerekse yurt dışında şu ana kadar gelecek beklentisi, psikolojik sağlamlık ve mutluluk korkusunun bir arada araştırıldığı çalışmalara rastlanmaması ve özellikle mutluluk korkusuyla ilgili sınırlı sayıda çalışmaların olması yeni çalışmalara gereksinim doğurmaktadır.…”
unclassified